The morphology and sedimentology of two unconsolidated quaternary debris slope deposits in the Alexandria district, Cape Province - Illgner, Peter Mark (Rhodes University, Faculty of Science, Department of Geography, 1995)
Research on hillslope surface processes and hillslope stratigraphy has been neglected in southern Africa. The amount of published literature on hillslope stratigraphy in southern Africa is very limited. Hillslope sediments provide a record of past environmental conditions and may be especially useful in calculating the recurrence interval of extreme environmental conditions such as earthquakes and intense rainfall events. The characteristics of hillslope sediments provide information as to their origin, transport and mechanisms of deposition. No published work could be found that had been undertaken on hillslope surface processes or stratigraphy in the eastern Cape coastal region. This study attempted to fill this gap in the geomorphic literature for southern Africa. The surface processes acting on hillslopes at Burchleigh and Spring Grove in the Alexandria district of the eastern Cape were examined in terms of slope morphology, surface sediment characteristics and the internal geometry of the hillslope sedimentary deposits. The late Quaternary hillslope sedimentary deposits at the two study sites are composed of fine grained colluvial sediments intercalated with highly lenticular diamicts. The fine grained colluvial sediments were emplaced by overland flow processes while the diamicts were deposited by debris flows. The sedimentary sequences at both study sites have a basal conglomerate interpreted as a channel lag deposit. Most slope failures preceding debris flow events were probably triggered by intense or extended periods of rainfall associated with cold fronts or cut-of flows. Seismic events may also have triggered slope failure, with or without the hillslope sediments being saturated. The results of this study indicate that a continuum exists between the slopewash dominated processes of the presently summer rainfall regions of Natal to the present winter rainfall regions of the western Cape where mass movement processes are significant. Hillslope deposits, therefore, provide a record of environmental conditions which may greatly facilitate proper management of the landscape.
Keywords: Slopes (Physical geography) -- South Africa; Weathering -- South Africa; Geomorphology -- South Africa